Performance-based standards for the road sector (Transport (Paris, France), 2005)
This report examines existing regulatory approaches and then explores how performance standards might be used to improve regulatory outcomes. Under a performance-based approach to regulation, standards would specify the performance required from vehicle operations rather than mandating how this level of performance is to be achieved. More flexible performance-based regulations provide for increased innovation and more rapid adoption of new technologies. The report explores the regulatory reform processes in some countries that have led to more direct, outcome-oriented approaches to regulating road transport vehicles.--Publisher's description.